Wide thermal range, exclusive occurrence of technically significant chiral nematic phase: synthesis and mesomorphism of cholesterol-based non-symmetric dimers - Nayak, Rashmi Ashwathama; Bhat, Sachin A.; Rao, D. S. Shankar; Yelamaggad, V. C. (Bulletin of Materials Science, 2020)
Fifteen new non-symmetric chiral dimers belonging to three different series have been synthesized and evaluated for their mesomorphic properties. They are formed by interlinking cholesterol with salicylaldimine (SAN) cores (with reverse imine groups) via an omega-oxyalkanoyloxy spacer. Within a series, the length of the terminaln-alkoxy tails has been varied for a fixed even-parity spacer. Three even-parity spacers such as 4-oxybutanoyloxy, 6-oxyhexanoyloxy and 8-oxyoctanoyloxy have been used to join two cores, whereas the terminal tails such asn-butyloxy,n-hexyloxy,n-octyloxy,n-decyloxy andn-dodecyloxy chains have been attached to the SAN core. Microscopic and calorimetric experimental results show that all the dimers behave identically exhibiting the chiral nematic (N*) phase solely, which was authenticated by powder X-ray diffraction studies carried out on some selected samples. In the vast majority of the cases, this phase is thermodynamically stable, and while cooling, it exists over a wide thermal range covering room temperature (RT) due to supercooling. This finding is notable given the fact that the N* phase possesses technologically significant optical properties. At RT, the N* phase displayed one of the iridescent colours characteristically caused by interference and diffraction of the reflected and scattered light. A comparative study reveals that the lengths of both the terminal chain and central spacer influence the clearing temperature of the dimers, and also the temperature range of the N* phase. The selective reflection measurements revealed that the pitch of the N* phase is either temperature sensitive or temperature insensitive. Temperature-dependent circular dichroism (CD) spectra were recorded for the planar texture of the N* phase formed by a dimer, as a representative case. The presence of an intense negative CD band suggests the left-handed screw sense of the N* phase helix.
Keywords: CD activity; cholesteric phase; dimers; liquid crystals; selective reflection